THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO, AND RETURN ON ASSET ON THE STOCK PRICE OF PT FAST FOOD INDONESIA Tbk - Shafa, Adinda Kamila; Herlinawati, Erna (Universitas Muhammadiyah Tangerang, 2025)
The study aims to analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Asset (ROA) on the Share Price of PT Fast Food Indonesia Tbk for the period 2014-2023. The research method used is quantitative with descriptive and verification approaches, and uses secondary data obtained from the company’s annual financial statement. Stock prices experienced significant fluctuations with a decrease that occured due to the COVID-19 pandemic and the issues of boycott conflicts that affected the company’s performance. The decrease in CR and the increase in DER reflect unhealthy financial conditions, while fluctuations in ROA indicate the effectiveness of unstable asset utilization. The analysis results show partially that CR, DER, and ROA do not have a significant influence on the Share Price. However, simultaneously shows that CR, DER, and ROA have a significant effect on Stock Price.